Developing a Set of Uniform Outcome Measures for Adult Day Services. (June 2020) - Anderson, Keith A.; Geboy, Lyn; Jarrott, Shannon E.; Missaelides, Lydia; Ogletree, Aaron M.; Peters-Beumer, Lisa; Zarit, Steven H.
Adult day services (ADS) provide care to adults with physical, functional, and/or cognitive limitations in nonresidential, congregate, community-based settings. ADS programs have emerged as a growing and affordable approach within the home and community–based services sector. Although promising, the growth of ADS has been hampered by a lack of uniform outcome measures and data collection protocols. In this article, the authors detail a recent effort by leading researchers and practitioners in ADS to develop a set of uniform outcome measures. Based upon three recent efforts to develop outcome measures, selection criteria were established and an iterative process was conducted to debate the merits of outcome measures across three domains—participant well-being, caregiver well-being, and health care utilization. The authors conclude by proposing a uniform set of outcome measures to (a) standardize data collection, (b) aid in the development of programming, and (c) facilitate the leveraging of additional funding for ADS.